(untitled) (Gaceta de Ciencias Veterinarias, 2018)
In order to carry out a structural characterization in the production units (UP) with dairy cattle of the Bisuquiu community, Boconó municipality of Trujillo state, Venezuela, a descriptive investigation was carried out, using a non-experimental, cross-sectional and field design, with elements of the Participatory Action Research. The data were analyzed using statistical procedures descriptive of the SAS® statistical package. The UP was identified as predominantly semi-intensive, operating under eminently family labor. The most used breed was the Holstein as a pure breed or crossed with other dairy breeds (Jersey, Brown Swiss, Carora). Among the technical-productive indicators were evaluated, the Animal Load (CA): 4.93 AU/ha, age of incorporation of heifers to the service: 24.28 months, weight of heifers before first service: 358.21 kg, production per farm: 14.28 liters/day, daily production: 7.83 liters/cow/day, lactation 2389 liters/cow/year. Improved pastures and food supplementation represent an aspect of utmost importance within the UP, which allows the adequate nutritional status of the herds. The 50% of the evaluated UP apply fertilization plans, 85.71% use manual methods for weed control, and irrigation was only found in 14.29% of the UP. The health plans cover the vaccinations required by the National Institute of Integral Agricultural Health (INSAI). The 85.71% of the UP combine their own consumption and the commercialization of the products (milk, curd and cheese); identifying a "producer- consumer" marketing chain, which demonstrates the importance of the consumption of dairy products in the community.